A Psychodynamic Psychologist in Community Psychiatry: 14 Years of Experience - Roquette, Tânia (2013)
This paper aims to critically review the role of a psychodynamic psychologist integrated in a community outpatient clinic of a Psychiatric Department. It describes the characteristics of a psychodynamic intervention that is complementary to the psychiatric approach while sharing a common goal –the suffering patient – and enhancing the knowledge and understanding of several domains like psychopathology, diagnosis, treatment, rehabilitation and integration. Furthermore it describes how the use of Psychological Assessment led to the formulation of specific individual psychotherapies, spanning 14 years of clinical practice. The paper concludes with some considerations regarding the integration of Psychodynamic Psychology in a multidisciplinary mental health team, addressing issues such as the boundaries between technical characteristics, the appropriateness of language to other disciplines and psychodynamic implications of the different features of this clinical setting.